Odonata from bahia solano, colombian pacific region (2020)
We present a checklist of Odonata species from Bahia Solano Municipality in the Pacific Region of Colombia. Sampling effort included 715 h between December 2018 and January 2020. We recorded 51 species in 27 genera and seven families. The most representative families were Libellulidae with 14 genera and 29 species and Coenagrionidae with 10 genera and 16 species. Argia fulgida Navás, 1934 and Erythrodiplax funerea (Hagen, 1861) are newly recorded from Chocó Department. The richer localities in terms of species numbers are conservation areas which are little impacted by indigenous traditional agriculture.